Hoitotyön opettajan osaaminen - Karjalainen, Tuula (fi=Turun yliopisto|en=University of Turku|, 2008)
The purpose of this study was to evaluate the competence of nurse teachers, who are teaching nursing at polytechnic level in Finland. The following research questions were framed for the study: What kind of evaluation nurse teachers of their nursing competence, teaching skills, evaluation skills, personality factors and relationships with students. The data were collected by a questionnaire (A Tool for Evaluation of Requirements of Nurse Teacher, ERNT). The questionnaire regarded background factors and 20 statements divided in five categories. The five competence categories were: Nursing competence, Teaching skills, Evaluation skills, Personality factors and Relationships with students. The evaluation scale was a 5-point Likert-scale. The respondents were nurse teachers, teacher for emergency nursing, public health nurse and midwifery teachers from all polytechnics in Finland. Response rate to the questionnaire was 46 % (n=342). The data were analysed by using descriptive statistics. Mean scores and standard deviations for each item were calculated. Category scores were obtained by summing scores of all items within a category. The results of this study showed that nurse teacher evaluated their competence on a high level. Concerning the category Relationships with students (mean 4.61, standard deviation 0.71) they got the highest averages. The lowest scores were gained regarding the requirements associated with teaching skills (mean 4.30, standard deviation 0.82). Concerning a single question, the best score was achieved in ability to take students seriously (mean 4.66, standard deviation 0.71) and the lowest score was achieved for their guidance of students to advance in decision making (mean 4.15, Std 0.69). The nurse teachers evaluated themselves with relatively high scores concerning competence categories as a hole. In future it is important to study nurse teacher competence with students or authorities of health service.

Tutkimuksen tarkoituksena oli kuvata hoitotyön opettajien osaamista heidän itsensä arvioimana. Tutkimusongelmina olivat: millaiseksi hoitotyön opettajat arvioivat oman hoitokompetenssin, opetustaito- ja arviointitaito-osaamisensa, omat persoonallisuuden piirteensä sekä osaamisensa suhteissa opiskelijoihin. Tutkimusaineisto kerättiin Opettajamittari2000© -mittarilla, joka koostuu 20:stä opettajan toimintaa kuvaavasta väittämästä. Kuhunkin opettajan osaamisen alueeseen kuuluu neljä väittämää. Arviointiasteikkona on viisiportainen Likert-asteikko, jossa 1 = toteutuu huonosti ja 5 = toteutuu erittäin hyvin. Kysely lähetettiin sekä sähköisesti että lomakekyselynä kaikille Suomessa toimiville hoitotyön, ensihoidon, kätilötyön ja terveydenhoitotyön opettajille. Vastausprosentti oli 46 % (n = 342). Aineisto analysoitiin tilastollisin menetelmin. Jokaiselle väittämälle laskettiin frekvenssi, keskiarvo ja keskihajonta. Pääkategorioita tarkasteltiin summamuuttujina suhteessa taustamuuttujiin. Parhaiten hoitotyön opettajien osaaminen toteutui heidän suhteissa opiskelijoihin (Ka 4.66, Kh 0.41) ja heikoiten toteutui opetustaito-osaaminen (Ka 4.37, Kh 0.51). Yksittäisistä väittämistä opettajien osaaminen toteutui parhaiten heidän ottaessaan opiskelijat tosissaan (Ka 4.72, Kh 0.51). Heikoiten opettajien osaaminen toteutui heidän ohjatessaan opiskelijoiden päätöksenteon kehittymistä (Ka 4.15, Kh 0.69). Hoitotyön opettajien osallistumisella täydennyskoulutukseen oli tilastollisesti merkitsevä yhteys opettajien arviointitaitojen osaamiseen (p = 0.0123) ja persoonallisuuden piirteistä johtuvaan osaamiseen (p = 0.0011). Myös hoitotyön opettajan koulutuksella oli tilastollisesti merkitsevä yhteys hoitokompetenssin osaamiseen (p = 0.024). Hoitotyön opettajat arvioivat oman osaamisensa erittäin hyväksi. Jatkossa tulee tutkia opettajien osaamista muiden, esimerkiksi opiskelijoiden ja terveydenhuollon palveluorganisaatioiden, näkökulmasta.